Structural and functional variations of octenyl succinylated clustered amylopectin produced by distinctive glycogen branching enzymes - Choi, Kyeong-Ok; Yim, Cheul-Soon; Nguyen, Phu Cuong; Park, Jong-Tae (Food science and biotechnology, 2025)
Clustered amylopectins (CAPs) were produced using recombinant glycogen branching enzymes from K12 (EcGBE) and (VvGBE). The CAPs were esterified with octenyl succinic anhydride (OSA), introducing novel functional characteristics. Vv-CAP demonstrated a reduced apparent molecular weight and a higher prevalence of both short (degree of polymerization (DP) ≤ 5, 13.3%) and medium branches (5 < DP ≤ 12, 58.2%) compared to Ec-CAP. FT-IR spectra confirmed the successful esterification of CAPs with OSA. H-NMR analysis showed the degree of substitution (DS) for OSA-CAPs varied based on the CAP to OSA ratio (DS 0.021-0.058 for Ec-CAP and 0.011-0.066 for Vv-CAP). Esterification with OSA on shortened branches resulted in a slower digestion rate and increased resistant starch proportion. Additionally, this process enhanced the emulsifying properties of CAPs and improved the aqueous solubility of puerarin. OSA-modified CAPs are promising for pharmaceutical applications. The online version contains supplementary material available at 10.1007/s10068-025-01892-1.